Gill chemoreceptors and cardio-respiratory reflexes in the neotropical teleost pacu, Piaractus mesopotamicus - Leite, C. A. C.; Florindo, L. H.; Kalinin, A. L.; Milsom, W. K.; Rantin, F. T. (Springer, 2007)
This study examined the location and distribution of O-2 chemoreceptors involved in cardio-respiratory responses to hypoxia in the neotropical teleost, the pacu (Piaractus mesopotamicus). Intact fish and fish experiencing progressive gill denervation by selective transection of cranial nerves IX and X were exposed to gradual hypoxia and submitted to intrabuccal and intravenous injections of NaCN while their heart rate, ventilation rate and ventilation amplitude were measured. The chemoreceptors producing reflex bradycardia were confined to, but distributed along all gill arches, and were sensitive to O-2 levels in the water and the blood. Ventilatory responses to all stimuli, though modified, continued following gill denervation, however, indicating the presence of internally and externally oriented receptors along all gill arches and either in the pseudobranch or at extra-branchial sites. Chemoreceptors located on the first pair of gill arches and innervated by the glossopharyngeal nerve appeared to attenuate the cardiac and respiratory responses to hypoxia. The data indicate that the location and distribution of cardio-respiratory O-2 receptors are not identical to those in tambaqui (Colossoma macropomum) despite their similar habitats and close phylogenetic lineage, although the differences between the two species could reduce to nothing more than the presence or absence of the pseudobranch.
Keywords: cardio-respiratory control; chemoreceptors; hypoxia; NaCN; pacu; Piaractus mesopotamicus